The benefits of black rice bran and the potential of its bioactive compounds as antidiabetic agents - Rafika Eviana; Nyoman Suci Widyastiti; Endang Mahati (AcTion: Aceh Nutrition Journal, 2023)
Prevention strategies for diabetes have been found to minimize the risk of the disease through lifestyle treatments such as physical exercise and nutrition. Plants with strong antioxidant activity have previously been discovered to be effective therapy for Type 2 Diabetes Mellitus. A total of 12 English articles were reviewed. Black rice bran, in its raw extract form, modulate the activity of enzymes, hormones, and molecular signaling related to glucose homeostasis in the body. Black rice bran increases the defense of pancreatic β cells against apoptosis. Bioactive substances in black rice bran such as anthocyanins, proanthocyanidins, γ-oryzanol regulate diabetes-related molecular signaling which ultimately leads to improvement in glucose levels, insulin levels, restoration and protection of pancreatic β cells against apoptosis. These bioactive substances are also possible in suppressing oxidative stress, increasing antioxidant status and decreasing inflammation which is a common condition in diabetes. The conclusion of this literature review was black rice bran has the potential to have an antidiabetic effect through various mechanisms, in which this effect is possible due to the bioactive substances contained in it.